2017
DOI: 10.3892/etm.2017.5135
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of zoledronic acid on articular cartilage and subchondral bone of rabbits with experimental knee osteoarthritis

Abstract: Subchondral bone reabsorption and remodeling are responsible for the initiation and progression of osteoarthritis (OA). Zoledronic acid (ZOL), a third-generation bisphosphonate (BIS), is an inhibitor of bone reabsorption. However, the intervention effect of ZOL on OA has not been fully characterized and remains to be directly demonstrated in animal experiments. The present study examined the microscopic and macroscopic changes in the anterior cruciate ligament transection (ACLT) model of OA in rabbits and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Preclinical studies included healthy animals of both sexes and were performed in rabbits (9 out of 26; 34.6%) and rats (9 out of 26; 34.6%), followed by mice (3 out of 26; 11.5%), guinea pigs (2 out of 26, 7.8%), and dogs (3 out of 26; 11.5%). In this review, in the majority of the studies that included dog and rabbit models, OA was surgically induced by anterior cruciate ligament transection (ACLT) and/or medial meniscectomy (MMT) [ 20 27 , 43 45 ]. Only one study in rabbits used intraarticular injection of chymopapain for chemically-induced OA [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical studies included healthy animals of both sexes and were performed in rabbits (9 out of 26; 34.6%) and rats (9 out of 26; 34.6%), followed by mice (3 out of 26; 11.5%), guinea pigs (2 out of 26, 7.8%), and dogs (3 out of 26; 11.5%). In this review, in the majority of the studies that included dog and rabbit models, OA was surgically induced by anterior cruciate ligament transection (ACLT) and/or medial meniscectomy (MMT) [ 20 27 , 43 45 ]. Only one study in rabbits used intraarticular injection of chymopapain for chemically-induced OA [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common type was alendronate, studied in 11 articles: two in rabbits [ 23 , 24 ], five in rats [ 31 33 , 35 , 37 ], three in mice [ 38 40 ], and one in guinea pigs [ 42 ]. It was followed by zoledronic acid with 7 articles: three in rabbits [ 20 , 21 , 28 ], three in rats [ 29 , 30 , 36 ], and one in dogs [ 43 ], and risedronate with 6 studies: four in rabbits [ 22 , 25 27 ], one in rats [ 35 ], and one in guinea pigs [ 41 ]. Two studies in dogs evaluated the effect of tiludronate [ 44 , 45 ], and only one study in rats focused on the effect of pamidronate [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, antiresorptive agents have been proposed as potential disease-modifying OA drugs. It is believed that bisphosphonates could modulate the subchondral bone remodeling and consequently inducing changes in the OA progression, reducing the cartilage degeneration ( 3 , 10 , 13 , 18 20 , 49 ). In previous preclinical studies, risedronate has shown a reduction in the cartilage pathology ( 50 ) and changes in cancellous bone microarchitecture leading to improved mechanical properties ( 17 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is an increasing interest in their application in OA (7,15,16). Treatment with BPs seems to induce a decrease in the severity of OA scores, showing less cartilage pathology and bone changes in experimental animal models such as rats (3,10,17,18), and rabbits (13,19,20). But it is still controversial whether these are effective in stopping the disease progression, because in some osteoarthritis preclinical research using guinea pigs (21), rats (14), and dogs (22), it was reported that the administration of BPs showed no effect on preventing the articular cartilage damage or even worsened the cartilage conditions in spite of greater subchondral bone quality.…”
Section: Introductionmentioning
confidence: 99%